The experiences of a tutor during the implementation of an applied behaviour analysis programme : a case study - Van Wyk, M. M. (Martha Magdalena) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEdPsych)--University of Stellenbosch, 2003.